Coulometric Karl-Fischer-Titration of Water in CAD/CAM Chairside Composites. (2022) - Faria-E-Silva, A.L.; Heckel, L.; Belli, R.; Lohbauer, U.
Abstract : Purpose/Aim: This study aimed to evaluate the water sorption of CAD/CAM chairside composites over 21 days using coulometric Karl-Fischer (KF) titration Materials and Methods: Rectangular plates (10 ×10 x 1 mm of thickness) were cut from the blocks of composites Cerasmart 270 (CS), Katana Avencia Block (KA), Grandio Blocs (GB) and Lava Ultimate (LU) (n = 15). Five specimens of each material were evaluated without any water storage, and the remaining was stored in distilled water for 7 or 21 days at 37 C. Coulometric KF titration of evaporated water content from specimens heated at 200 C (Isothermal) was carried out to measure the water content. The water vapor was transferred to a methanol solution in the Coulometer throughout a nitrogen gas flow. The mass of extracted water was measured in real-time until reach a drift of 5 g/min. Data were analyzed by 2-way ANOVA and Tukey`s post hoc test (α = 0.05). Results: The water content of non-stored specimens ranged from 0.29 0.01% (7.1 0.3 μg/mm 3 ) to 1.66 0.14% (33.9 2.3 μg/mm 3 ) for GB and LU, respectively. The water content increased for all materials after 7 days (ranged from 0.72 0.03% to 2.90 0.06%) in water but storing the specimens for further 14 days only increased the content for CS (from 1.47 0.15% to 1.71 0.01%). After 21 days in water, the lowest water sorption was observed for GB (10.9 μg/mm 3 ) and the other materials absorbed approximately 20.0 μg/mm 3 . The variation coefficient of readings reduced from the non-stored specimens (4.9-11.8%) toward specimens stored for 21 days (0.8-3.1%). Conclusions: Chairside composites present some base water content that is not measured by ISO 4049. KF titration demonstrates to be a reliable method to measure the water sorption of composites, including their base content. Further studies are required to determine the effect of water sorption on hydrolytic expansion and expansion stress of these materials.